Intrinsic motivation toward engagement in physical activity (PA) among secondary schools students of Sekolah Menengah Kebangsaan Agama, Kuala Lumpur / Mohamad Faizal Adenan - Adenan, Mohamad Faizal (Faculty of Education, 2014)
The level of physical activity is usually influenced by the high motivation factors. There are many motivating factors such as internal and external factors. This study is carried out to determine and investigate the factor of intrinsic motivation that influence people in sport participation and level of physical activity. There were 220 respondents involved in this study; the people who involve are students of Sekolah Menengah Kebangsaan Agama Kuala Lumpur. Questionnaires were administered for all form four and form five students in order to obtain information and responses regarding their intrinsic motivation factors. The survey is based on the source of "Sport Motivation Scale" (SMS) and the "International Physical Activity Questionnaire" (IPAQ), which was subsequently edited to meet the needs of the study. The data collected via the questionnaire was calculated manually and the findings were tabulated, and then presented in an orderly and easy-to-read manner in SPSS system. The findings of this study observe the factors of intrinsic and level of physical activity and sport participation among students that involved in their daily live activities. The results showed positive significance between intrinsic motivation and physical activity as well as the differences between men and women.